Strategi Pemasaran Produk Sosis Siap Makan (Studi Kasus: PT Primafood Internasional ) - Wibowo, Mohamad Emir; Daryanto, Arief; Rifin, Amzul (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
Problems faced by fast food products in the form of sausage from PT Primafood International with the brand Champ is lost competitor with competitors and sales tend to fluctuate throughout the year. This study was conducted with the objectives formulated from the description of the background. This research aims to 1) Identify internal and external factors of the company in marketing ready-to-eat sausage products, 2) Formulate strategies that can be done by companies to improve the marketing of ready-to-eat sausage on the market regarding products, prices, promotion and distribution. 3) Recommend the best strategy from various alternative strategies that can be formulated The method of analysis used is SWOT analysis. The result of this research is the formulation of alternative marketing strategy obtained by external and internal factors is to cooperate with partner, product differentiation, joint promotion with Charoen Pokphand group, and educative promotion. Based on the SWOT-ANP results, it is found that educational promotion is the priority of the main strategy recommended.